Synthesis, Spectral Studies and Normal Coordinate Analysis of 2,6-Diphenyl-3-Methyl Piperidone - Chithambarathanu, T.; Umayorubhagan, V.; Krishnakumar, V. (Asian Journal of Chemistry, 2010)
2,6-Diphenyl-3-methyl piperidone has been synthesised and characterised using spectroscopic tools. The FTIR spectrum of this compound has been interpreted by assuming Cs point group symmetry. The normal coordinate analysis has also been carried out by applying Wilson's FG matrix mechanism.